2′-Fucosyllactose Ameliorates Inflammatory Bowel Disease by Modulating Gut Microbiota and Promoting MUC2 Expression - Yao, Qianqian; Fan, Linlin; Zheng, Nan; Blecker, Christophe; Delcenserie, Véronique; Li, Huiying; Wang, Jiaqi (Frontiers in Nutrition, 2022)
Gut microbiota dysbiosis, together with goblet cells dysfunction has been observed in ulcerative colitis cases. This study aims to evaluate the potential of 2'-fucosyllactose （2'-FL）supplementation in inhibiting intestinal inflammation through regulating gut microbiota, protecting goblet cells and stimulating mucin secretion. 2'-FL was orally administered to C57BL/6J mice daily (400 mg/kg b.w.) for 21 days, and 5% dextran sulfate sodium (DSS) was used to induce the colitis in the last 7 days. Meanwhile, fecal microbiota transplantation (FMT) was conducted to test the roles of gut microbiota in the remission of colitis by 2'-FL. Gut microbiota alteration was analyzed through 16S rRNA sequencing. Periodic acid-Schiff (PAS), immunofluorescence staining, as well as MUC2 and NLRP6 mRNA expression in colon fragments were performed and detected. The results showed that the DSS+2'-FL mice were found to have a slower rate of weight loss, lower disease activity index (DAI) scores and longer colon lengths than the DSS group (P＜0.05), so did in the FMT recipient mice which received fecal microbiota from the DSS+2'-FL group. In addition, the data revealed that 2'-FL relieved the disorder of DSS-induced gut microbiota, including decreasing high abundance of mucin-utilizing bacteria in DSS group, such as Bacteroides, Lachnospiraceae NK4A136, Lachnospiraceae and Bacteroides vulgatus. PAS and immunofluorescence staining showed that 2'-FL treatment promoted the recovery of goblet cells and enhanced MUC2 and NLRP6 expression, which was also observed in the FM(DSS+2'-FL) group. Moreover, NLRP6, which, has been proved to be a negative regulator for TLR4/MyD88/NF-κB pathway, was up-regulated by 2'-FL in colon tissue. In conclusion, this work suggests that 2'-FL ameliorates colitis in a gut microbiota-dependent manner. The underlying protective mechanism associates with the recovery of goblet cells number and improves MUC2 secretion through TLR4-related pathway.